Biocontrol potential of native entomopathogenic nematodes in controlling red hairy caterpillar (Amsacta albistriga) (Lepidoptera :Arctiidae) of groundnut (Arachis hypogaea) - BASKARAN, R K MURALI; SIVAKUMAR, C V; VENUOOPAL, M S (The Indian Journal of Agricultural Sciences, 2013)
The efficacy of an entomopathogenic nematode, Steinernema carposapsae Weiser (strain DD 136), and3 native isolates. designated Heterorhabditis bacteriophora Poinar (strain Burliar). Heterorhabditis sp (strain Chekkanurani) and Heterorhaditis sp (strain Melur). was tested during 1992 for controlling fourth-instar larvae of red hairy caterpillar [Amsacta albistriga (Walker)] of ground nut (Arachis hypogaea L.). The nematode was used at 5 concentrations (0,5, 10,20 and 40 infective juveniles/larva) and estimated Lethal concentration 50 (LT50). The efficacy of the nematode depended on its population level. Among the4 nematodes. S. carpocapsae was the most effective in killing the larvae, followed by Heterorhabditis sp (strain Chekkanurani). having LC50 respectively 6.5 and 8.3 nematodes/larva at 84 hr after inoculation. Similarly. LT50@ 20 infective juveniles/larva was 3.1-5.5 days. Absence of dauers in the dead larvae indicated that the host tissue prevented the development of 3 native Heterorhabditis sp. But the host insect died because of symbiotic bacterial population, whereas S. carpocapsae killed the host by completing its life-cycle.